QSAR Studies of Pyridazine Derivatives as Tuberculostatic Agents - PRATAP SINGH, HEMENDRA; NEMA, R.K.; SINGH, ANOOP; D. GUPTA, SAYAN (Asian Journal of Chemistry, 2010)
QSAR studies have been done by taking a series of pyrazine derivatives exhibiting tuberculostatic activity against (1) Mycobacterium tuberculosis strain H37 Rv, (2) Mycobacterium tuberculosis strain 109, isolated from a patient, resistant to isoniazid, ethambutol and refampcin (3) Mycobacterium tuberculosis strain 193, isolated from a patient fully susceptible to tuberculostatic and by using openstate 4 version 6.5.1 statistical software. The studies were carried out on 15 analogs. These studies produced good predictive models and give statistically significant correlations of hydrophobic and molar refractivity in R1 position of the compounds, which are having significant correlation with all the tubercular strain.